FPR3 orchestrates macrophage polarization in breast cancer: multi-omics dissection of prognostic relevance and therapeutic targeting - Ying Chen; Xin Tang; Liran Zhu; Yi Wang; Gaopeng Li; Wulin Yang (Cancer Cell International)
Abstract Background The N-formyl peptide receptor family (FPRs) is implicated in the progression of diverse cancer types, yet studies specifically exploring their roles in breast cancer remain scarce. Methods A comprehensive analysis integrating bulk RNA-seq transcriptomics, methylomics, single-cell transcriptomics, and spatial single-cell transcriptomics data was conducted to elucidate the distinctive characteristics of FPRs in breast cancer. This study particularly focused on delineating the e xpression profiles of FPR3 across distinct breast cancer subtypes, while systematically investigating its prognostic implications and association with macrophage polarization patterns in breast cancer patients. Furthermore, molecular docking analysis was performed to screen potential therapeutic compounds targeting FPR3, providing insights into its druggability. Results Notably, FPR3 was found to be highly expressed in macrophages within breast cancer tissues, with a notably elevated level in HER2-positive and triple-negative breast cancer (TNBC) subtypes, both of which are associated with poor prognosis. FPR3 expression inversely correlates with promoter methylation levels. Further analysis of pan-cancer immune infiltration patterns uncovered a striking association between FPR3 and macrophage infiltration, as well as their polarization status. Knockdown of FPR3 expression in macrophages markedly enhanced the expression of IL6, TNF-α, and TGF-β, while significantly reducing IL10 levels, indicative of a shift towards an M1-like macrophage phenotype. Through computational molecular docking analyses, Otamixaban and Rivaroxaban emerged as promising candidate inhibitors of FPR3. Conclusions These findings underscore the profound infiltration of FPR3 + macrophages in breast cancer patients with adverse prognoses, highlighting FPR3 as a potential therapeutic target for intervening breast cancer aggressiveness.